VD_FINDINFO Décision / 2022 / 916 vom 23. Dezember 2022 - VD Tribunal cantonal (2022)
DISJONCTION DE CAUSES, UNITÉ DE LA PROCÉDURE, DOMMAGE IRRÉPARABLE | 29 al. 2 Cst., 29 CPP (CH), 30 CPP (CH), 385 al. 1 CPP (CH), 393 al. 1 let. b CPP (CH), 396 al. 1 CPP (CH)